Faktor-Faktor yang Mempengaruhi Return Saham Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017 - Dylen Limto; Carunia Mulya Firdausy (Universitas Tarumanagara, 2020)
The purpose of this research is to analyze the effect of Earning Per Share, Debt to Equity Ratio, Return on Assets, and Current Ratio on Stock Return in manufacturing companies listed in Indonesia Stock Exchange for the period of 2015 until 2017. This research used 198 data from manufacturing companies listed in Indonesia Stock Exchange, selected using purposive sampling method. The statistical method used to analyze the data in this research is multiple linear regression. The result of this research shows that earning per share and debt to equity ratio have no significant effect on stock return, return on assets and current ratio have significant effect on stock return.